Shonjibon cash transfer and nutrition counselling trial in rural Bangladesh - the impact on women's empowerment - Kirkwood, Elizabeth (University of Sydney, 2019)
Presented by Elizabeth Kirkwood (The University of Sydney), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.